Modeling and Simulation of Dual-band Yagi Antennas for Voice Communication on Microsatellite - Muhammad Darsono; Ahmad Ruri Wijaya; Rommy Hartono (JURNAL INFOTEL, 2019)
The design of the dual-band Yagi antenna was developed to support voice communication through voice repeaters on microsatellites in the UHF-VHV frequency from ground stations. The Yagi antenna is a type of half lambda dipole antenna that makes it easy to obtain direction and increase gain. The antenna is designed using the method of moment through a simulation with the CST microwave studio software application. The design used as an antenna element material is a type of copper pipe cylinder. The results of the Yagi antenna design in the VHF frequency consist of one driven element, one reflector element, and three director elements, while the UHF frequency consists of one reflector element and seven directors. The results of simulation parameters are obtained, such as Bandwidth of return loss below 10 dB is 4.3 MHz(VHF), and 44 MHz (UHF), VSWR (2:1) is 1.24 (VHF) and 1.36 (UHF), Gain is 9.19 dBi (VHF) and 10.5 dBi (UHF) and Beam Width is 64 degree (VHF) and 58 degree (UHF). The suitability of the antenna design target is dual-band, and Gain value in UHF is higher than VHF.